RADON DOSIMETRY USING CR_39 AS A TRACK DETECTOR
Solid state nuclear detector (CR-39) was used to obtain the concentration level of radon and itsdaughters, by using (Ra-266) of (10.54mCi) activity. It was employed for radon concentration andpotential alpha energy exposure level. It is found increasing in track density with (absorbed dose,WLM, radon concentration in (PCi/liter), and potential alpha energy (PAEC)). The calibrationcurves were drawn by taking the linear part from the above curves. There is decreasing inabsorbed dose with distance from the source. The linear response determine the detectorrange of (300-3X104 Bq/m3), and the calibration factors was obtained for calibration(0.2